Powszechność ochrony ubezpieczeniowej - Szpunar, Janusz (Wydział Prawa i Administracji UAM, 1968)
Among fundamental principles of economic insurances in socialistic countries is the principle of universal insurance protection. In literature on this subject, however, this principle is treated not so much from the statistic-economic point of view, as primarily in the aspect of legal questions concerning the limitations of insurance protection. Yet, backed by various premises which justify the claim of the insurers to making the most in the field of insurances, we get a somewhat different notion of this principle, of a specific quantitative significance. Of the most general premises to the universality of insurance protection, we should mention in the first place the insurance grounds. In a way, the insurance socialises individual losses by passing the charge of coverage from the individual onto the whole endangered community. The greater the community the more the number and magnitude of losses to be covered can be precisely anticipated, and, at the same time, the less their weight is felt. Economic and social reasons speaking for the application of insurance protection in different circumstances justify the wide range of subjects and objects thus protected. Hence, social and economic values of a number of insurances appeal for the extension of insurance protection to as many subjects and objects as possible who are threatened by various dangers. In some cases, social interests can only be insured when the insurance protection is universal. Then, legislation makes the universal insurance independent from individual insurance by introducing obligatory insurances. However, their scope does not provide a full picture of the realisation of the discussed principle, especially even when with the considerable extension of this type of insurances, the voluntary insurances are exploited to a low degree.
Universal Insurance Protection